2019
DOI: 10.25077/jka.v8.i1.p68-75.2019
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Jus Seledri (Apium graveolens L.) terhadap Gambaran Mikroskopis Hepar Tikus (Rattus norvegicus) yang Diinduksi Diet Hiperkolesterol

Abstract: Kadar kolesterol berlebihan dalam tubuh akan mengakibatkan penumpukan lemak di hepar. Salah satu alternatif obat tradisional yang dapat menurunkan kadar kolesterol adalah tanaman seledri. Penelitian sebelumnya menyatakan bahwa fraksi air herba seledri dapat menurunkan kadar kolesterol total pada keadaan hiperkolesterol. Tujuan penelitian ini adalah menentukan pengaruh pemberian jus seledri terhadap gambaran mikroskopis hepar yang diinduksi diet hiperkolesterol pada tikus percobaan. Jenis penelitian adalah eksp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…The result other study showed that Apium grafeolens could reduce fatty acid in rat hepar on an effective dose of 0.72 mL/200 g Body Wheight [9]. This indicated that Apium grafeolens could reduce cholesterol content at hyper cholesterol conditions.…”
Section: Resultsmentioning
confidence: 76%
“…The result other study showed that Apium grafeolens could reduce fatty acid in rat hepar on an effective dose of 0.72 mL/200 g Body Wheight [9]. This indicated that Apium grafeolens could reduce cholesterol content at hyper cholesterol conditions.…”
Section: Resultsmentioning
confidence: 76%
“…On histopathological examination of the liver, it was found that the liver cells near the central vein were swollen due to fat degeneration and the sinusoids looked irregular. 3 In Hahn's research in Heriansyah, giving a high-fat diet to rats caused an increase in total cholesterol levels. It caused a hypercholesterolemic condition after being given a high-fat diet for five weeks, but there was no decrease in HDL levels.…”
Section: Discussionmentioning
confidence: 99%
“…2 Excessive cholesterol levels in the body will result in fat accumulation in the liver. 3 In pregnant women, there is also a significant increase in the concentration of lipids, lipoproteins, and apolipoproteins in plasma. This fat storage occurs mainly in mid-pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Biji dan buahnya berkhasiat sebagai antispasmodik, menurunkan kadar asam urat darah, antirematik. Seledri juga berkhasiat sebagai penenang (sedatif), peluruh kentut (karminatif), pereda nyeri (antiinflamasi), antioksidan, antibakteri, anti kanker dan juga antihipertensi (Dewi et al, 2016;Dwinanda, Afriani, & Hardisman, 2019;Syahidah & Sulistyaningsih, 2018)…”
Section: Seledriunclassified
“…Seledri mengandung fitosterol yang merupakan komponen fitokimia yang berguna untuk melawan kolesterol. Fitosterol dalam seledri berfungsi mencegah aterosklerosis, komplikasi akibat disfungsi endotel oleh hipertensi (Dwinanda et al, 2019). Magnesium dan zat besi pada seledri dapat membersihkan sisa metabolism dan simpanan lemak yang berlebih dalam pembuluh darah.…”
Section: Kandungan Kimia Seledri Dan Potensi Sebagai Antihipertensiunclassified